The effect of macroeconomic variables on non performance financing of Islamic Banks in Indonesia - Latifah Dian Iriani; Imamudin Yuliadi (Economic Journal of Emerging Markets, 2015)
This research is going to discuss about the determinant macro variables and bank’s behavior determinant credit risk on Islamic rural bank in Indonesia. It could be seen on macro variables such as inflation, exchange rate, Jakarta I slamic index (JII) and money supply (M2), and bank’s behavior such as financing. Research methodology used at this study is Vector Error Correction Model (VECM). Following these procedures, it applies Unit Roots Test, Augmented Dickey Fuller Test, Lag Length Criteria Test, Correlation Matrix – Johansen Julius Co-integration Test, VECM Estimation, Impulse Response and Variance Decomposition Test. The result show that both bank behaviors and macroeconomic variables are significant affecting non-performing financing (NPF). The banking need more careful to manage internal and external factors that influence non-performing financing (NPF).